Barriers to Accessing Kidney Transplantation Among Populations Marginalized by Race and Ethnicity in Canada: A Scoping Review Part 2—East Asian, South Asian, and African, Caribbean, and Black Canadians. (March 2021) - El-Dassouki, Noor; Wong, Dorothy; Toews, Deanna M.; Gill, Jagbir; Edwards, Beth; Orchanian-Cheff, Ani; Neves, Paula; Marshall, Lydia-Joi; Mucsi, Istvan
Background: Kidney transplantation (KT), a treatment option for end-stage kidney disease (ESKD), is associated with longer survival and improved quality of life compared with dialysis. Inequities in access to KT, and specifically, living donor kidney transplantation (LDKT), have been documented in Canada, along various demographic dimensions. In this article, we review existing evidence about inequitable access to KT and LDKT for patients from communities marginalized by race and ethnicity in Canada. Objective: To characterize the currently published data on rates of KT and LDKT among East Asian, South Asian, and African, Caribbean, and Black (ACB) Canadian communities and to answer the research question, "what factors may influence inequitable access to KT among East Asian, South Asian, and ACB Canadian communities?." Eligibility criteria: Databases and gray literature were searched in June and November 2020 for full-text original research articles or gray literature resources addressing KT access or barriers in East Asian, South Asian, and ACB Canadian communities. A total of 25 articles were analyzed thematically. Sources of evidence: Gray literature and CINAHL, OVID Medline, OVID Embase, and Cochrane databases. Charting methods: Literature characteristics were recorded and findings which described rates of and factors that influence access to KT were summarized in a narrative account. Key themes were subsequently identified and synthesized thematically in the review. Results: East Asian, South Asian, and ACB communities in Canada face barriers in accessing culturally appropriate medical knowledge and care and experience inequitable access to KT. Potential barriers include gaps in knowledge about ESKD and KT, religious and spiritual concerns, stigma of ESKD and KT, health beliefs, social determinants of health, and experiences of systemic racism in health care. Limitations: This review included literature that used various methodologies and did not assess study quality. Data on ethnicity and race were not reported or defined in a standardized manner. The communities examined in this review are not homogeneous and views on organ donation and KT vary by individual. Conclusions: Our review has identified potential barriers for communities marginalized by race and ethnicity in accessing KT and LDKT. Further research is urgently needed to better understand the barriers and support needs of these communities, and to develop strategies to improve equitable access to LDKT for the growingly diverse population in Canada.